Mr. Chickee's funny money [compact disc, unabridged] - Curtis, Christopher Paul (Listening Library, 2005)
Flint Future Detective Club members Steven Carter, his friend Russell, and Russell's huge dog Zoopy solve the mystery of a quadrillion-dollar bill with the image of James Brown on it.